Relationism and the Problem of Publicity. (19th December 2021) - Valente, Matheus; Verdejo, Víctor M.
Abstract: According to a recently developed family of relational views, whether two concepts C1 and C2 are the same is a matter of an external relation in which their tokens stand. In this paper, we highlight the chief contributions of Relationism in the elucidation of concept sameness, present a set of arguments to the effect that relational accounts of concept sameness fail to accommodate a substantive notion of concept publicity, and offer a diagnosis of this result. We conclude that the strengths of non‐relational approaches will also need to be considered in order to fully capture what it means for a concept to be public.